Osteogenesis imperfecta, tricho‐dento‐osseous syndrome and intellectual disability: A familial case with 17q21.33‐q22 (COL1A1 and DLX3) deletion and 7q32.3‐q33 duplication resulting from a reciprocal interchromosomal insertion. Issue 10 (15th August 2013) - Harbuz, Radu; Bilan, Frédéric; Couet, Dominique; Charraud, Valérie; Kitzis, Alain; Gilbert‐Dussardier, Brigitte
ABSTRACT We report on a 22‐year‐old woman with features of osteogenesis imperfecta (OI), tricho‐dento‐osseous (TDO) syndrome and intellectual disability. Whole genome oligonucleotide microarray analysis revealed a copy number gain of 3 Mb in 7q32.3‐q33 and a loss of 3.4 Mb in 17q21.33‐q22. FISH analysis showed that the third copy of 7q32 was inserted into the long arm of one chromosome 17, exactly in the region 17q21.33‐q22 that was deleted. The maternal uncle presented with clinical features similar to the proposita and had the same chromosomal anomalies. The mother of the proposita and two other family members were balanced carriers of this rearrangement, interpreted as an interchromosomal reciprocal insertion. Reciprocal insertion/four‐break rearrangement is a very rare chromosomal event. The deleted region on chromosome 17 contains 39 genes, including COL1A1 and DLX3 involved in OI and TDO syndrome respectively. The CACNA1G gene on the deleted segment of chromosome 17 may be a good candidate gene to explain the intellectual impairment. © 2013 Wiley Periodicals, Inc.